Perencanaan Publik Relation MS Cosmetic Dalam Meningkatkan Brand Awareness Pada Produk Peel Off Nail Polish (representamen, 2023)
The emergence of factories providing maklon services in the cosmetics industry has intensified competition in the cosmetics and beauty business. The number of competitors in the cosmetics industry makes people faced with many cosmetic choices, this making the cosmetic brand MS Cosmetic by MS Glow must be able to compete and get its position in society. This study aims to describe the Public Relations communication planning carried out by MS Cosmetic in increasing Brand Awareness to the public through MS Cosmetic's new product, Peel Off Nail Polish. This research uses descriptive qualitative methods with data collection techniques of interviews, observation and documentation. The concept used in the study uses the five-step model planning stages of Hafied Cangara and the results obtained that the Public Relations planning carried out by MS Cosmetic in increasing Brand Awareness by conducting research on the target market, then endorsing well-known artists or influencers through social media, participating in various beauty events, evaluating and reporting to the leadership of MS Cosmetic Keywords : Communication Planning, Public Relations, MS Cosmetic, Brand Awareness